Tobacco leaf FI protein doped composite nanofiber air filtering membrane and preparation method thereof
By adding tobacco leaf FI protein to the air filter membrane material and using electrospinning technology, the problem of insufficient filtration efficiency and stability of existing air filter materials is solved, and the comprehensive utilization of high-efficiency filtered air pollutants and resources is achieved, reducing the Environmental pollution and energy consumption.
Patent Information
- Application Number
- CN202411684254.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-01-07
AI Technical Summary
The existing air filter materials have shortcomings in filtration efficiency and stability, especially the hydrophobicity and stability of electrospun nanofiber membrane materials, which leads to low filtration efficiency and easy blockage. In the processing and use of traditional air filter materials There are problems of resource waste and environmental pollution.
By adding tobacco leaf FI protein to the polymer, the hydrophobicity is improved by combining its amino acid with the hydroxyl group of polyvinyl alcohol, and a high-performance nanofiber air filter membrane is prepared through electrospinning technology to improve filtration efficiency and stability, while effectively utilizing tobacco Waste, reduce environmental pollution.
Achieve efficient filtering of air pollutants, especially PM2.5, improves filtration efficiency and stability, reduces gram weight, extends service life, and effectively utilizes tobacco waste, reduces environmental pollution, and creates society and economy. benefit.
Smart Images

Figure CN119258807A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of air filtration nanofiber membrane materials, and specifically relates to a composite nanofiber air filtration membrane doped with tobacco leaf FI protein and a preparation method thereof. Background Art
[0002] The rapid economic development and the continuous acceleration of industrialization inevitably bring about environmental damage, accelerating the increase of inhalable particulate matter, volatile organic compounds and greenhouse gases in the air. Fine particulate matter (PM) can enter the human body through the breathing process, threatening human health. According to the preliminary compilation and reference of the list of carcinogens published by the World Health Organization's International Agency for Research on Cancer, outdoor air pollution is on the list of Class I carcinogens. In order to solve the shortcomings of traditional air filtration materials, high-performance nanofiber membranes used in the field of air filtration are required to have high filtration efficiency, low air resistance, large specific surface area, high porosity (up to 80% or more), low gram weight, good stability, etc., which can more effectively eliminate particulate pollution in the air.
[0003] At present, the core functional layer of the filter responsible for removing PM is mainly made of non-woven fabrics or ultra-fine glass fibers. Due to the limitation of their specific surface area, particulate matter deposits and clogs during filtration, increasing resistance and energy consumption. In addition, glass fibers are brittle and are easily broken during processing and use, affecting their use. The service life and dust-proof and dust-absorbing capabilities of the filter membrane are gradually unable to meet actual needs, so electrospun nanofiber membranes with smaller fiber diameters and higher specific surface areas have received widespread attention.
[0004] In order to meet the requirements of material functionalization, electrospinning technology can provide a simple, efficient and easy-to-control process to manufacture high-performance air filtration nanofibers. PVDF, PES and PVA are common membrane materials, but the products prepared by using these polymers alone or in blends have defects such as poor filtration efficiency, high gram weight and poor stability.
[0005] my country is a major tobacco-growing country, with a planting area of approximately 133×10 4 hm 2 The annual output is about 240×10 4 t, both ranking first in the world. In the process of tobacco planting and processing, a large amount of tobacco waste such as low-grade tobacco leaves, tobacco stems, tobacco dust and tobacco seeds is generated, accounting for about 25% of the total tobacco leaf production. At present, there are very few ways to comprehensively utilize these wastes, and the degree of comprehensive utilization is very low. Most of them are discarded as waste, which also causes great pollution to the environment. Summary of the invention
[0006] The purpose of the present invention is to solve the shortcomings of the prior art and provide a composite nanofiber air filtration membrane doped with tobacco leaf FI protein and a preparation method thereof. By adding FI protein and combining it with a polymer, a high-performance air filtration membrane modified with nanoscale fibers with stable structure and good performance is obtained through electrospinning. The nanofiber membrane has high filtration efficiency and large specific surface area, can efficiently filter air pollutants, and has high stability.
[0007] To achieve the above object, the present invention provides a composite nanofiber air filter membrane doped with tobacco leaf FI protein, the raw materials of the air filter membrane include: polymer, FI protein, the fiber diameter range is 230-780nm, the gram weight is 6-50g / m 2 .
[0008] Preferably, the polymer is one or a mixture of any proportion of polyvinylidene fluoride (PVDF), polyethersulfone (PES), and polyvinyl alcohol (PVA).
[0009] Due to the poor hydrophobicity of polyvinyl alcohol, which is a hydrophilic polymer, if its hydrophobicity is not improved, it will cause holes in the fiber defects on the surface of the prepared membrane, resulting in a significant reduction in the filtration efficiency. By adding tobacco leaf FI protein, the amino acids in the protein combine with the hydroxyl groups in polyvinyl alcohol to improve film-forming properties, thereby improving hydrophobicity, which is beneficial to the preparation of nanofiber filtration membranes and further improves the filtration efficiency. The FI protein contains a full range of amino acids, and the content of various essential amino acids in the FⅠ protein is higher than the standards set by FAO, among which lysine, arginine, histidine, glutamic acid, etc. are polar charged amino acids. In addition, the FⅠ protein also contains many non-polar and hydrophobic groups. The increase in charged groups enhances the adsorption capacity, which enhances the ability of the nanofiber membrane to adsorb particulate matter and has a higher filtration efficiency for PM2.5.
[0010] Further preferably, when the polymer is polyvinylidene fluoride, PVDF:FI protein = 20.5-34.5:0.25-2.5; when the polymer is polyethersulfone, PES:FI protein = 23-25:0.1-5; when the polymer is polyvinyl alcohol, PVA:FI protein = 13-14.5:0.2-2; when the polymer is a mixture of polyvinylidene fluoride and polyethersulfone, PVDF:PES:FI protein = 11.5-14:11.5-14:0.2-2.5.
[0011] It is further preferred that polyethersulfone be dried before use. Because polyethersulfone has a relatively high water absorption, drying is extremely important. Failure to dry will increase the difficulty of spinning, and changes in viscosity will destroy stability and fluidity; the fiber morphology will be abnormal, and uneven charges will cause the fiber to be beaded or broken; it will be difficult to stretch after absorbing water, reducing the collection efficiency; the performance will be reduced, the surface will be rough, and the appearance and performance will be affected.
[0012] The air filtration membrane of the present invention creatively proposes to add FI protein, which solves the problem of waste and pollution of tobacco waste on the one hand, and improves the hydrophobicity, stability and filtration efficiency of the air filtration membrane on the other hand. After adding FI protein, the present invention has different effects with PVA, PES and PVDF respectively. Since polyvinyl alcohol has poor hydrophobicity, polyvinyl alcohol (PVA) is a hydrophilic polymer. If its hydrophobicity is not improved, it will cause holes in the fiber defects on the membrane surface, resulting in a significant reduction in filtration efficiency. By adding tobacco leaf FI protein, the amino acids in the protein combine with the hydroxyl groups in polyvinyl alcohol to improve film-forming properties, thereby improving hydrophobicity and further improving filtration efficiency; FI protein is integrated into PES, and the free α-amino group (-NH2) at the N-terminus and the free α-carboxyl group (-COOH) at the C-terminus of its peptide chain are utilized. By introducing carboxyl groups, amino groups or other polar groups into PES, the film-forming properties and stability of the material can be improved; FI protein also contains many non-polar, hydrophobic and hydrophilic groups, such as carboxyl groups (-COOH), amide groups (-CONH2) and amines (-NH2 and -NH3 + ), which makes the PVDF nanofiber membrane more stable after adding FⅠ protein; the content of various essential amino acids in FⅠ protein is high, which is higher than the standard of essential amino acids in protein products established by FAO. Among them, lysine, arginine, histidine and glutamic acid are polar charged amino acids. The many non-polar, hydrophobic and hydrophilic groups contained in FⅠ protein enhance the ability of nanofiber membrane to adsorb particulate matter and have a higher filtration efficiency for PM2.5.
[0013] A method for preparing a composite nanofiber air filter membrane doped with tobacco leaf FI protein comprises the following steps:
[0014] (1) dissolving the polymer in a solvent, heating and stirring to eliminate bubbles, and adding FI protein after cooling to room temperature to form a uniform and stable spinning solution;
[0015] (2) Using the spinning solution in step (1) to perform electrospinning, a composite nanofiber air filtration membrane with stable structure and good performance is obtained.
[0016] Preferably, the mass fraction of the solute in the spinning solution is 12-25%.
[0017] Further preferably, the solvent in step (1) is one of N,N-dimethylacetamide (DMAC) and acetone (ACE) or any ratio of the two; the solvent is a mixture of N,N-dimethylacetamide and acetone, and the weight ratio is N,N-dimethylacetamide:acetone=70:30. Taking advantage of the low boiling point and fast volatilization rate of ACE, the use of a mixed solution of DMAC and ACE can accelerate the volatilization of the solvent during the spinning process, and the obtained fibers are uniform, which can effectively avoid the generation of beads and film spots.
[0018] More preferably, in terms of weight ratio, when the polymer is polyvinylidene fluoride (PVDF), PVDF:N,N-dimethylacetamide:acetone = (20.5-34.5):70:30; PES:N,N-dimethylacetamide = (23-25):(73-76.8); PVA:N,N-dimethylacetamide = (13-14.5):100; PVDF:PES:N,N-dimethylacetamide:acetone = (11.5-14):(11.5-14):70:30.
[0019] Preferably, in step (2), the electrospinning conditions are: spinning time 4-6h, temperature 21-28°C, humidity 50-75%. Further preferably, in step (2), the spinning conditions are: spinning voltage 10-15kV, receiving distance 8-15cm, liquid supply rate 0.002-0.010mL / min, and drum speed 12rpm.
[0020] Adding FI protein to the polymer spinning solution has a great influence on the conditions of electrospinning, because the physicochemical properties of FI protein, such as solubility, surface activity and charge characteristics, will change the rheological behavior and conductivity of the solution, thereby affecting the electrospinning process, and ultimately affecting the performance of the product. After continuous exploration, the inventors continuously optimized and adjusted the process parameters to make the spinning process proceed normally and prepare a filter membrane with excellent performance. The present invention is beneficial to film formation by increasing the temperature and reducing the humidity, accelerating the volatilization of the solvent and the solidification of the fiber. Too high or too low temperature and humidity will destroy the uniformity of the fiber and affect the fiber transformation; too high temperature will cause the solvent to volatilize too quickly, making the fiber surface uneven, and a beaded or honeycomb structure will appear, affecting the morphology and quality of the fiber. If the temperature is too low, the solvent will evaporate slowly, and the fiber solidification time will be long, resulting in uneven fiber diameter, affecting the film-forming effect; reducing humidity will help accelerate the volatilization of the solvent, and dry air can take away the evaporated solvent molecules faster. If the humidity is too high, the water vapor in the air may compete with the solvent for evaporation, slowing down the volatilization rate of the solvent and affecting the formation and uniformity of the fiber; electrospinning The principle of spinning is to spray the spinning solution into many extremely fine fibers through the electric field force. The voltage directly affects the amount of charge on the surface of the droplet and the size of the interaction force with the electric field. Under the same other spinning conditions, when the voltage is too low, the polymer is not completely ionized and the fibers appear in a beaded form. When the voltage is too high, the fibers are strongly stretched, accompanied by bifurcation and splitting. The spinning time and the liquid supply rate are the main reasons affecting the gram weight of the nanofiber membrane. The mass of the membrane per square meter can be controlled by controlling the time and speed. For example, a long spinning time and a high liquid supply rate can obtain a high gram weight and a thicker nanofiber membrane. A short spinning time and a low liquid supply rate can obtain a low gram weight and a thinner nanofiber membrane.
[0021] Preferably, the extraction method of FI protein is: extraction, heat precipitation, centrifugation, and drying. The method is simple and easy to operate, and can effectively extract FI protein from tobacco waste such as low-grade tobacco leaves, tobacco stems, tobacco dust, and tobacco seeds.
[0022] Further preferably, the extraction method of FI protein is: fully crush the tobacco leaves, mix and stir the crushed tobacco leaves with a phosphate buffer solution, the pH value is required to be 7.0-8.0, the solid-liquid ratio is 1:10-15, fully homogenize, refrigerate for 5-6 hours for extraction, filter the liquid with 200 mesh gauze, adjust the pH to 8.0, heat sink temperature to 40-60°C, 0.5-1h, cool to room temperature, centrifuge, wash, and dry to obtain FI protein.
[0023] The beneficial effects of the present invention are as follows:
[0024] (1) Extracting and utilizing FI protein from tobacco waste such as low-grade tobacco leaves, tobacco stems, tobacco dust and tobacco seeds effectively utilizes resources, turns waste into treasure, avoids environmental pollution, and creates social and economic benefits.
[0025] (2) The addition of FI protein improves the film-forming property, hydrophobicity, and stability, and enhances the adsorption effect of the air filtration membrane.
[0026] (3) The addition of FI protein in a reasonable proportion avoids the formation of spindles and is beneficial to the electrospinning process.
[0027] (4) Selecting a suitable solvent can make the obtained fibers uniform and effectively avoid the formation of beads and film spots.
[0028] (5) The air filtration membranes prepared using electrospinning technology have nanometer-scale fiber diameters, low gram weight, and adjustable fiber diameter and shape, which gives them significant advantages in filtration (adsorption) performance. They can effectively intercept particulate matter in the air and have a good filtration effect on particles such as haze and PM2.5. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a simplified process diagram of electrospinning;
[0030] Figure 2 This is a scanning electron microscope image of the product of Example 1;
[0031] Figure 3 This is a scanning electron microscope image of the product of Example 2;
[0032] Figure 4 This is a scanning electron microscope image of the product of Example 3;
[0033] Figure 5 This is a scanning electron microscope image of the product of Example 4;
[0034] Figure 6 This is a scanning electron microscope image of the product of Example 5;
[0035] Figure 7 This is a scanning electron microscope image of the product of Comparative Example 1;
[0036] Figure 8 This is a scanning electron microscope image of the product of Comparative Example 2;
[0037] Fig. 9 The infrared spectra of the products of Examples 1-5 and Comparative Examples 1-2 are shown;
[0038] Fig.10 Thermogravimetric curves of the products of Examples 1-4;
[0039] Fig.11 It is the thermogravimetric curve diagram of the products of Example 2, Example 5 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0040] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0041] In the following, the average molecular weight of polyvinylidene fluoride is 400,000, purchased from Arkema (Suzhou) Polymer Materials Co., Ltd.; polyether sulfone (PES) is from BASF (China) Co., Ltd.; polyvinyl alcohol 1788 type, alcoholysis degree: 87.0-89.0% (mol / mol), purchased from BASF (China) Co., Ltd.
[0042] Extraction of FI protein: First, weigh 7.8059g of sodium dihydrogen phosphate dihydrate and 7.1053g of disodium hydrogen phosphate (anhydrous) and dissolve them in 1000mL of water respectively. Then, mix the two solutions to obtain a phosphate buffer solution with a pH of 7.45-7.8. Grind and crush the dried low-grade tobacco leaves, stems, tobacco dust and seeds, mix them with the phosphate buffer solution at a solid-liquid ratio of 1:10, stir for a period of time to make the slurry sufficient, place the mixed liquid in a low temperature environment (4°C) for 5h and then filter it with 200 mesh gauze. Collect the filtrate and adjust it to pH 8.0 with 1mol / L NaOH solution. Then, heat the filtrate in a water bath for 0.5h at 40°C, cool it to room temperature, and centrifuge it at 3000r / min for 10min. Add an equal volume of distilled water to the supernatant to wash the precipitate, dry it in a vacuum oven at 40°C for 24h, and finally grind it to obtain FI protein powder.
[0043] The following examples all use FI protein extracted by this method. In actual production and application, other methods can also be used to extract FI protein or FI protein products can be directly purchased.
[0044] Example 1
[0045] A method for preparing a composite nanofiber air filter membrane doped with tobacco leaf FI protein:
[0046] 3.0723g of polyvinylidene fluoride was weighed and dissolved in a mixed solvent of 10.5g of N,N-dimethylacetamide and 4.5g of acetone, heated in a water bath at 80°C and stirred for 2h until completely dissolved, cooled to room temperature, 0.0904g of FI protein powder was added and stirred thoroughly to obtain a uniformly mixed and stable spinning solution. The spinning process conditions were: spinning time 5h, temperature 26.6°C, humidity 68%, spinning voltage 12kV, receiving distance 13cm, liquid supply rate 0.010mL / min, drum speed 12rpm, screw needle 21G; fiber diameter: 100 fibers in the electron microscope image were selected to measure the average diameter of 378.67nm, and the gram weight was: 45g / m 2 .
[0047] Example 2
[0048] A method for preparing a composite nanofiber air filter membrane doped with tobacco leaf FI protein:
[0049] Before use, polyethersulfone was dried at 60°C for 24h using a blower dryer, 3.748g of polyethersulfone was weighed and dissolved in 14.055g of N,N-dimethylacetamide, heated in a 70°C water bath and stirred for 3h until completely dissolved, cooled to room temperature, 0.0937g of FI protein powder was added and stirred thoroughly to obtain a uniformly mixed and stable spinning solution, and the spinning process conditions were: spinning time 6h, temperature 27.1°C, humidity 66%, spinning voltage 12kV, receiving distance 13cm, liquid supply rate 0.002mL / min, drum speed 12rpm, screw needle 20G; fiber diameter: 100 fibers in the electron microscope image were selected to measure the average diameter of 236.16nm, and the gram weight was: 6.19g / m 2 .
[0050] Example 3
[0051] A method for preparing a composite nanofiber air filter membrane doped with tobacco leaf FI protein:
[0052] 1.8367g polyvinyl alcohol was weighed and dissolved in 14.055g N,N-dimethylacetamide. The mixture was heated in a water bath at 95°C and stirred for 5h until completely dissolved. After cooling to room temperature, 0.0799g FI protein powder was added and stirred thoroughly to obtain a uniformly mixed and stable spinning solution. The spinning process conditions were as follows: spinning time 6h, temperature 27.2°C, humidity 75%, spinning voltage 11kV, receiving distance 13cm, liquid supply rate 0.005mL / min, drum speed 12rpm, screw needle 20G; fiber diameter: 100 fibers were selected from the electron microscope image and measured, and the average diameter was 322.34nm, and the weight was 10.31g / m 2 .
[0053] Example 4
[0054] A method for preparing a composite nanofiber air filter membrane doped with tobacco leaf FI protein:
[0055] 1.7593 g of polyethersulfone and 1.7593 g of polyvinylidene fluoride were weighed and dissolved in a mixed solvent of 10.5 g of N, N-dimethylacetamide and 4.5 g of acetone, heated in a water bath at 80°C and stirred for 2 h until completely dissolved, cooled to room temperature, added with 0.931 g of the FI protein powder in Example 1 and stirred thoroughly to obtain a uniformly mixed and stable spinning solution. The spinning process conditions were: spinning time 5 h, temperature 26.4°C, humidity 67%, spinning voltage 11 kV, receiving distance 13 cm, liquid supply rate 0.008 mL / min, drum speed 12 rpm, screw needle 22 G; fiber diameter: 100 fibers in the electron microscope image were selected to measure their diameters, and the average value was 772.39 nm, and the gram weight was: 24.88 g / m 2 .
[0056] Example 5
[0057] A method for preparing a composite nanofiber air filter membrane doped with tobacco leaf FI protein:
[0058] Before use, polyethersulfone was dried at 60°C for 24h using a blower dryer, 4.6822g of polyethersulfone was weighed and dissolved in 14.055g of N,N-dimethylacetamide, heated in a 70°C water bath and stirred for 3h until completely dissolved, cooled to room temperature, 0.0028g of FI protein powder was added and stirred thoroughly to obtain a uniformly mixed and stable spinning solution, and the spinning process conditions were: spinning time 6h, temperature 21.2°C, humidity 53%, spinning voltage 12kV, receiving distance 13cm, liquid supply rate 0.002mL / min, drum speed 12rpm, screw needle 20G; fiber diameter: 100 fibers in the electron microscope image were selected to measure their diameters, and the average value was 269.98nm, and the gram weight was: 5.4375g / m 2 .
[0059] Comparative Example 1
[0060] A method for preparing an electrospinning composite nanofiber air filter membrane:
[0061] Before use, polyethersulfone was dried at 60°C for 24h using a blower dryer, 4.685g of polyethersulfone was weighed and dissolved in 14.055g of N,N-dimethylacetamide, heated in a 70°C water bath with stirring for 3h until completely dissolved, and cooled to room temperature to obtain a uniformly mixed and stable spinning solution. The spinning process conditions were: spinning time 6h, temperature 24.2°C, humidity 72%, spinning voltage 12kV, receiving distance 13cm, liquid supply rate 0.002mL / min, drum speed 12rpm, screw needle 20G; fiber diameter: 100 fibers in the electron microscope image were selected to measure their diameters, and the average value was 359.68nm, and the gram weight was: 17.125g / m 2 .
[0062] Comparative Example 2
[0063] A method for preparing a composite nanofiber air filter membrane doped with tobacco leaf FI protein:
[0064] Before use, polyethersulfone was dried at 60°C for 24h using a blower dryer, 3.748g of polyethersulfone was weighed and dissolved in 14.055g of N,N-dimethylacetamide, heated in a 70°C water bath and stirred for 3h until completely dissolved, cooled to room temperature, 0.937g of FI protein powder was added and stirred thoroughly to obtain a uniformly mixed and stable spinning solution, and the spinning process conditions were: spinning time 6h, temperature 20.9°C, humidity 65%, spinning voltage 12kV, receiving distance 13cm, liquid supply rate 0.002mL / min, drum speed 12rpm, screw needle 20G; fiber diameter: 100 fibers in the electron microscope image were selected to measure their diameters, and the average value was 247.16nm, and the gram weight was: 4.875g / m 2 .
[0065] Test example
[0066] Air filtration efficiency:
[0067] According to GB3095-2012, the air filter membranes prepared in Examples 1-5 and Comparative Examples 1-2 have different filtering effects at different times. The specific test data are as follows:
[0068] Table 1 shows the air filtration efficiency of the air filtration membranes obtained in Examples 1-5 and Comparative Examples 1-2.
[0069]
[0070] It can be seen from the test data in Table 1 that in a short period of time, the filtration efficiency of Examples 1-4 is above 99%, while the filtration effect of Comparative Examples 1-2 is less than 99%; Comparative Example 1 does not add FI protein relative to Example 2, and its filtration efficiency is significantly lower than that of Example 2. As time goes by, the filtration efficiency of Example 2 does not decrease, but the filtration efficiency of Comparative Example 1 decreases significantly; Comparative Example 2 adds an excessive amount of FI protein relative to Example 2. Although the filtration efficiency is slightly increased relative to Comparative Example 1, the filtration efficiency does not reach 99%, and as time goes by, the filtration efficiency decreases more.
[0071] Figure 1 This is a simplified diagram of electrospinning in the present invention. Figure 2-8 The scanning electron microscope images of the products of Examples 1-5 and Comparative Examples 1-2 are shown; Fig. 9 The infrared spectra of Examples 1-5 and Comparative Examples 1-2 are shown in FIG. 1 , which show that FI protein is added to Examples 1-5 and Comparative Example 2, but no FI protein is added to Comparative Example 1; Fig.10 is the thermogravimetric curve of Examples 1-4, Fig.11 The thermogravimetric curves of Example 2, Example 5 and Comparative Examples 1-2 are shown. It can be seen from the graphical curves that Example 2, Example 5 and Comparative Example 2, to which FI protein is added, have better stability and are more conducive to air filtration applications in high-temperature fields. Comparative Example 1 does not add FI protein, and its stability is significantly poorer.
[0072] The filtration efficiency of commercial masks is about 95%, and the weight is about 102g / m 2 , the filtration efficiency is low and the gram weight is heavy. The maximum gram weight in the present invention is only 45g / m 2 , the filtration efficiency can reach 99.52%, which is a significant improvement over the prior art. The composite nanofiber air filtration membrane doped with tobacco leaf FI protein protected by the present invention not only effectively reduces the gram weight, but also improves the filtration efficiency and stability. The air filtration membrane prepared by the present invention has the advantages of low gram weight, high filtration efficiency, high stability, etc., and has important economic value and environmental benefits.
[0073] The present invention provides a composite nanofiber air filtration membrane doped with tobacco leaf FI protein and a preparation method thereof. The prepared air filtration membrane has a large specific surface area and a high porosity, can enhance air circulation, better capture particulate matter in the air, and achieve high-efficiency and low-resistance air filtration performance; the added tobacco leaf FI protein improves film-forming properties, stability and filtration performance; the utilization of tobacco leaf waste avoids waste of resources, reduces environmental pollution, and "turns waste into treasure"; reduces energy consumption, saves costs, and creates social and economic benefits; from the practical application aspect, the air filtration membrane prepared by electrospinning technology has broad application prospects.
[0074] The above is only the embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application should be included in the scope of the claims of the present application.
Claims
1. A composite nanofiber air filtration membrane doped with tobacco leaf FI protein, characterized in that: The raw materials of the fiber air filter membrane include: polymer, FI protein, the fiber diameter is 230-780nm, the gram weight is 6-50g / m 2 .
2. The composite nanofiber air filtration membrane doped with tobacco leaf FI protein according to claim 1, characterized in that: The polymer is one of polyvinylidene fluoride, polyether sulfone and polyvinyl alcohol or a mixture of several of them in any proportion.
3. The composite nanofiber air filtration membrane doped with tobacco leaf FI protein according to claim 2, characterized in that: When the polymer is polyvinylidene fluoride, PVDF:FI protein=20.5-34.5:0.25-2.5; When the polymer is polyethersulfone, PES:FI protein=23-25:0.1-5; When the polymer is polyvinyl alcohol, PVA:FI protein=13-14.5:0.2-2; When the polymer is a mixture of polyvinylidene fluoride and polyethersulfone, PVDF:PES:FI protein=11.5-14:11.5-14:0.2-2.
5.
4. The method for preparing a composite nanofiber air filtration membrane doped with tobacco leaf FI protein according to any one of claims 1 to 3, characterized in that: The steps include: (1) dissolving the polymer in a solvent, heating and stirring to eliminate bubbles, and adding FI protein after cooling to room temperature to form a uniform and stable spinning solution; (2) Using the spinning solution in step (1) to perform electrospinning, a composite nanofiber air filtration membrane with stable structure and good performance is obtained.
5. The method for preparing a composite nanofiber air filtration membrane doped with tobacco leaf FI protein according to claim 4, characterized in that: In step (1), the mass fraction of the solute in the spinning solution is 12-25%.
6. The method for preparing a composite nanofiber air filtration membrane doped with tobacco leaf FI protein according to claim 4, characterized in that: The solvent in step (1) is one of N,N-dimethylacetamide and acetone or both of them in any ratio.
7. The method for preparing a composite nanofiber air filtration membrane doped with tobacco leaf FI protein according to claim 6, characterized in that: The solvent is a mixture of N,N-dimethylacetamide and acetone, with a weight ratio of N,N-dimethylacetamide:acetone=70:
30.
8. The method for preparing a composite nanofiber air filtration membrane doped with tobacco leaf FI protein according to claim 4, characterized in that: In step (2), the electrospinning conditions are: spinning time 4-6h, temperature 21-28°C, and humidity 50-75%.
9. The method for preparing a composite nanofiber air filtration membrane doped with tobacco leaf FI protein according to claim 8, characterized in that: In step (2), the spinning conditions are: spinning voltage 10-15 kV, receiving distance 8-15 cm, liquid supply rate 0.002-0.010 mL / min, and drum speed 12 rpm.
10. The method for preparing a composite nanofiber air filtration membrane doped with tobacco leaf FI protein according to claim 1, characterized in that: The extraction method of the FI protein comprises: leaching, heat precipitation, centrifugation and drying.